KECAP RUNDAYAN BINARUNG RARANGKÉN BARUNG JEUNG GABUNG DINA NOVÉL SI BEDOG PANJANG KARYA KI UMBARA - Elis Siti Sa'adah, - (2023)
The background of this research is the lack of understanding of the Sundanese people in Sundanese itself, because it is rarely used. Apart from that, there is also a new pattern of confix and ambifix in Ki Umbara's novel Si Bedog Panjang. The purpose of this study is to describe 1) words affixed with confix and ambifix in the novel Si Bedog Panjang; 2) confix and ambifix; 3) affixation function; 4) grammatical meaning of confix and ambifix affixes. This research uses a qualitative approach with a descriptive method, through literature study. As for the source of data in this study, namely the novel Si Bedog Panjang by Ki Umbara. The result of this study is the discovery of 31 confixes and ambifixes of 232 words that have affixes. Based on the affix structure, in this study found 31 word patterns with confix and ambifix affixes. Meanwhile, based on their function, there are 24 affixes with inflective functions as well as 19 affixes with derivative functions. There are also those based on grammatical meanings, found 29 meanings. And the meaning that often appears is the meaning of 'affected by work D'.